Notational analysis of the State championship of Bosnia and Herzegovina and Balkans championship in judo for male competitors - Kajmovic, H.; Rado, I.; Crnogorac, B.; Mekic, A. (Homosporticus, 2011)
Main goal of this research is used notational analysis to define differences of the indicators of the situation efficiency among senior male from participants of the State championship of Bosnia and Herzegovina and Balkan`s Judo Championships. Analysis has been done based on video scripts of 109 fights for BIH senior`s male and video scripts of 79 fights for Balkan senior`s male in all seven categories. Matches have been monitored with 18 variables of situation`s efficiency in Judo. For defining differences of indicators of situation`s efficiency it has been used ÷2 (Chi Square) test. The results of the ÷2 tests implicate to the statistically important differences among seniors - male in analyzed indicators of the situation`s efficiency. Both groups of the examined were more efficient with throwing techniques comparing to the floor techniques. Bosnian seniors male used more hand throwing techniques while male Balkan championship dominated with leg throwing techniques and grappling techniques. The most efficient techniques that seniors - male used from BH State competitors are: Ippon Seoi Nage, Tani Otoshi, Harai Goshi, etc, while male competitors from Balkans championship used: Uchi Mata, Sukui Nage, Ippon Seoi Nage, etc.